Study on the Ground Pressure Manifestation Patterns of Roof Cutting and Pressure Relief - Runhu Zheng; Bingyuan Hao; Chaoyao Shi; Tongxi Li (Applied Sciences)
Pillarless mining technology is of great significance for improving coal recovery rates, but the intense mining-induced stress disturbances on gob-side entries often lead to surrounding rock instability. In this study, we focused on the ground control challenges in the headgate of Panel 81308 at Huayang Mine No. 2. Comprehensive monitoring of roof–floor convergence, rib deformation, and support resistance revealed the gob-side entry retaining deformation mechanisms with roof-cutting pressure relief; the results show that this retaining deformation exhibits the following three phases of characteristics: the rapid, decelerated, and stable stages. The average roof–floor convergence (607 mm) was significantly greater than the average rib deformation (170 mm), with floor heave accounting for 72.6% of total convergence. The coal pillar side showed dominant deformation in rib movements. The mining influence zones can be divided, based on their distances behind the working face, into strong disturbance zones (0–88 m), weak disturbance zones (88–142 m), and stabilized zones (>178 m). The cable bolt support system demonstrated advanced response characteristics. Compared with conventional gob-side entry retaining, the roof-cutting pressure relief technique altered stress transmission paths, significantly reduced roof load transfer efficiency, and effectively controlled roadway convergence, providing technical guidance for safe production in both this panel and mines with similar geological conditions.